New Bis-1,3,4-Thiadiazoles Based on Fumaric Acid: Preparation, Structure Elucidation, Antibacterial Activities, and Quantum-Chemical Studies - Muğlu, Halit; Yakan, Hasan; Elefkhakry, Ghaith Alabed Ibrayke; Altuner, Ergin Murat; Çavuş, M. Serdar (Slovenian Chemical Society, 2023)
New bis-1,3,4-thiadiazoles 1–7 were obtained by the reaction of fumaric acid and N-(alkyl/aryl/cyclic)thiosemicarbazides in the presence of phosphorous oxychloride. The structures of all compounds were elucidated by FT-IR, 1H NMR, and 13C NMR and elemental analysis. Antibacterial activity of the compounds was studied for eight selected bacteria. Compounds 2–7 exhibited effect on Klebsiella pneumoniae. However, none of the compounds effect on Pseudomonas aeruginosa, Staphylococcus epidermidis, Salmonella enterica serovar Kentucky, Serratia marcescens. Self-consistent reaction force (SCRF) calculations were performed in DMSO medium to examine solvent energies using CPCM and SMD models. 6-31G(d) and 6-311++G(2d,2p) basis sets were used for DFT calculations. Besides electronic parameters such as electronegativity, electrophilicity and spectroscopic examinations of the compounds, QTAIM, local electron affinities, and Fukui analyses were also performed. Theoretical approaches supporting the experimental observations revealed that compounds containing aromatic and cyclic groups exhibit stronger antibacterial behavior than compounds containing aliphatic groups.
Keywords: 3. Good health